Pengaruh Ekstrak Daun Mimba terhadap Perkembangan Antraknos pada Apel Manalagi Pascapanen - Ika Roostika Tambunan; Christanti Sumardiyono (Jurnal Perlindungan Tanaman Indonesia, 1997)
Neem leaf extract inhibitss spore germination of Colletotrichum gloeosporioides. Leaf extract obtained by Soxhlet method is better than leaf extract obtained by boiling water method. The extract inhibits development of anthracnose disease on manalagi apple up to nine days after spraying.